SENGKETA PERJANJIAN TIDAK BERNAMA : PENYELESAIAN DAN MEKANISME HUKUM NON-NAMED AGREEMENT DISPUTES: SETTLEMENT AND LEGAL MECHANISM - Rizka Nurhanifa Amelia; Shaffa Nathaniela; Yasmeen Auliandini Arafah; Nirindah Daniella Sembiring; Surahmad, Surahmad (Cahaya Ilmu Bangsa, 2024)
Unnamed agreement or innominaat agreement is an agreement that is not specifically regulated in law. This agreement was born from the principle of freedom of contract in society so that according to the needs of the community and the name of the agreement will be adjusted to the needs of the parties entering into the agreement. This has led to a lot of conflicts or disputes over unnamed agreements. Unnamed agreement disputes in contract law often pose complex legal challenges, given the lack of clarity regarding the specific arrangements in this unnamed agreement and the resolution of disputes that arise. Using a qualitative method, this article will discuss the validity of agreements, the principle of freedom of contract, identify the main sources of disputes related to non-named agreements and effective dispute resolution.